Pelaksanaan Keamanan Bagi Narapidana di Lembaga Pemasyarakatan Kelas II A Pekanbaru - Al Rusdi; Erdianto Effendi; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Class IIA Penitentiary institutions Pekanbaru also not independent security and public order disturbances. Types of security problems found in the Institute Penitentiary Class IIA Pekanbaru include: runaway, fights between fellow prisoners and detainees, theft of goods belonging to fellow inmates, riots and so forth. The purpose of writing this essay to examine the implementation of security for inmates at the Penitentiary Class II A Pekanbaru, obstacles in the implementation of security for inmates at the Penitentiary Class II A Pekanbaru and efforts made in overcoming obstacles to the implementation of security inmates at Penitentiary Class II A Pekanbaru.This type of research is legal research sociological research that is done by holding the identification law and how the effective implementation of the law in force in the community, or reviewing the situation through field problems associated with aspects applicable law. Source data used primary legal materials, secondary and tertiary.From the results of this study concluded, the implementation of security for Prisoners in Penitentiary Class II A Pekanbaru carried out in accordance with Standard Operating Procedures SOPs or owned by any guard or any security and guarding and supervision by cooperating with the Mobile Brigade and the Police. Obstacles in the implementation of security for inmates at the Correctional Institution Class IIA Pekanbaru are: lack of personnel security officer Pekanbaru Penitentiary Class IIA, not all of them armed security officers in perform duty to secure the inmates at the Correctional Institution Class IIA Pekanbaru dn their uncooperative behavior such prisoners , attempt to escape. Efforts to overcome obstacles in the implementation of security for inmates Penitentiary Class II A Pekanbaru is to increase the number of personnel security officer Pekanbaru Penitentiary Class IIA, improving Human Resources for security officers prisons, limiting the space for inmates. Keywords: Security For Inmates, Prison.